2016
DOI: 10.18632/oncotarget.10634
|View full text |Cite
|
Sign up to set email alerts
|

TERT promoter mutations in melanoma render TERT expression dependent on MAPK pathway activation

Abstract: The mechanism of telomerase re-activation in cancer had remained elusive until the discovery of frequent mutations in the promoter of the TERT gene that encodes the catalytic reverse transcriptase subunit of telomerase. We investigated the regulation of TERT expression in melanoma cell lines and our results show that promoter mutations render TERT expression dependent on MAPK activation due to oncogenic BRAF or NRAS mutations. Mutations in the TERT promoter create binding sites for ETS transcription factors. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 28 publications
3
66
0
Order By: Relevance
“…Furthermore, differences between previous studies and the present study may be due to the absence of investigation of LVI and necrosis in many of the above-mentioned studies. However, various molecular alterations accompanying the BRAF V600 mutation may also be features of an ordinary nevus, such as promoter mutations of telomerase reverse transcriptase (TERT) (27,28); mutations in NRAS, PTEN, CDK2NA, STK19, KIT, GNAQ, GNA11 and NF 1 genes (29)(30)(31) or undetected interactions between the BRAF V600 mutation and other signaling pathways (26). Further studies on genotypic and phenotypic alterations in specimens of primary tumours obtained from both metastatic and nonmetastatic patients may provide more information about the impact of the BRAF mutation on prognostic features of melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, differences between previous studies and the present study may be due to the absence of investigation of LVI and necrosis in many of the above-mentioned studies. However, various molecular alterations accompanying the BRAF V600 mutation may also be features of an ordinary nevus, such as promoter mutations of telomerase reverse transcriptase (TERT) (27,28); mutations in NRAS, PTEN, CDK2NA, STK19, KIT, GNAQ, GNA11 and NF 1 genes (29)(30)(31) or undetected interactions between the BRAF V600 mutation and other signaling pathways (26). Further studies on genotypic and phenotypic alterations in specimens of primary tumours obtained from both metastatic and nonmetastatic patients may provide more information about the impact of the BRAF mutation on prognostic features of melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported evidence that confirm this possibility for cooperation between TERT promoter and BRAF/RAS mutations. Vallarelli and coworkers (Vallarelli et al 2016) described that in melanoma, TERT promoter mutations provided a direct link between TERT expression and MAPK pathway activation due to BRAF or NRAS mutations via the transcription factor ETS1, that would bind to the mutated promoter leading to the re-expression of TERT. Also, in non-small-cell lung cancers (NSCLC), Liu and coworkers described that KRAS mutations increased TERT mRNA expression and telomerase activity by activating the RAS/MEK pathway, which contributes to the aggressive phenotype of NSCLC (Liu et al 2016b).…”
Section: Tert Promoter Mutations In Thyroid Cancermentioning
confidence: 99%
“…Telomerase reverse transcriptase (TErT), a catalytic subunit of telomerase that includes an rnA component (TErC), therewithal maintains the telomere homeostasis and chromosomal integrity (15). reactivation of TErT has been detected in approximately 90% of human cancers (3,(17)(18)(19)(20). This study attempted to investigate whether immunohistochemical expression of TErT differs in neoplastic and nonneoplastic pituitary tissues and aimed to investigate whether TErT expression is related to clinicopathological features of pituitary adenomas.…”
Section: Comparisons Of Cytoplasmic Tert Expression With Clinicopathomentioning
confidence: 99%
“…It is said that higher levels of electron transport system (ETS) transcription factors induce MMP1 expression and cause tumour invasion in pituitary adenomas (1). One of the most recent reports investigating the TErT expression in malignant melanoma has concluded that mutations in TErT promoter create additional binding sites for ETS transcription factors, particularly ETS1, and finally activates the mitogen-activated protein kinase (MAPk) pathway and cell proliferation (19). PTTG1 is a member of the securin family and is highly expressed in hormonesecreting invasive pituitary adenomas (1).…”
Section: Comparisons Of Cytoplasmic Tert Expression With Clinicopathomentioning
confidence: 99%
See 1 more Smart Citation